The Kingdom without Gratitude. Oikos and the Nature in the Era of Technology - Cuozzo, Gianluca (Religija ir kultūra, 2013)
Human beings have, with the help of technology, turned themselves into the like of enormous mouths to feed, an image which seems to stem from Pieter Bruegel’s fantasy. The environment, reduced to a dumping ground populated by nightmarish rats and paranoia, is left to take the fall of this consumeristic greed. This vampirism is the symbol of an individual reduced to a mere consumer, a parasitical being, intent on the depredation of every resource of natura naturans. Some artistic images, from Michaelangelo to C. D. Friedrich, can teach us to achieve a correct relationship with the world, thus avoiding Icarus’s delirium, the delirium of a precursor of the eccentric existence of homo oeconomicus. There is not much time left, we need to take immediate action and fix our common home, the Great Being, before it is too late. The planet, filled by our waste, is in great danger.
Keywords: nature; beauty; world; image; Leonardo da Vinci; knowing; consuming; Günther Anders; Hans Blumenberg; Jean Baudrillard